Influence of pH on fluorescent dissolved organic matter photo-degradation. (15th November 2015) - Timko, Stephen A.; Gonsior, Michael; Cooper, William J.
Abstract: A novel semi-continuous excitation emission matrix (EEM) fluorescence and absorbance monitoring system has been developed. Full EEMs were collected simultaneously with absorbance spectra every 20 min during 24 h solar-simulated irradiation experiments, and the kinetic change of fluorescence of Suwannee River natural organic matter IHSS standard material (SRNOM) at various pH values was investigated. Parallel factor analysis (PARAFAC) was then used to isolate the photo-labile and pH-influenced fluorescent components of SRNOM. Kinetic analysis showed increasing rates of fluorescence loss with increasing pH. This has significant implications for the photo-degradation of dissolved natural organic matter during estuarine mixing, when large increases of pH are common. The influence of pH on fluorescence and photo-degradation kinetics emphasizes the need for pH to be monitored and accurately controlled during laboratory experiments. It is also highly recommended that when constructing PARAFAC models or monitoring changes in fluorescence data between samples of different origins, that the pH be held constant to remove any potential artifacts or misinterpretation of data. Graphical abstract: Highlights: A novel photo-degradation system was designed to measure loss of DOM fluorescence. Photo-degradation of fluorescent DOM increased with pH. pH effects were not seen on photochemical changes in absorption spectra. Studies of fluorescent DOM must incorporate pH control.